Preparation method and application of novel magnetic response polyether demulsifier

Through the preparation of a new magnetically responsive polyether deemulsifier, the composite material of Fe3O4 magnetic nanoparticles and multi-wall carbon nanotubes was used to solve the problem of demulsification of high-water crude oil emulsions, and the rapid demulsification and magnetic response recovery were achieved, which improved the Demulsification effect and resource utilization rate.

CN119192604APending Publication Date: 2024-12-27CHANGZHOU UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411459575.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

It is difficult for existing deemulsions to effectively treat crude oil emulsions with high moisture content and complex compositions, and high molecular weight chemical deemulsions remain in the aqueous phase or oil phase after use, affecting the oil quality and production efficiency.

Method used

Using the preparation method of a new magnetic responsive polyether deemulsifier, Fe3O4 magnetic nanoparticles are synthesized by ferric chloride hexahydrate and anhydrous sodium acetate at high temperature, and grafted with mixed polyether deemulsifier to combine with multi-walled carbon nanotubes. Magnetic responsive composite material is formed for demulsification.

Benefits of technology

It realizes rapid demulsification of high-water O/W emulsions, reduces demulsifier residues, improves oil-water separation efficiency, and is recycled through external magnetic fields, significantly improving the demulsification effect and resource utilization.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119192604A_ABST
    Figure CN119192604A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a novel magnetic response polyether demulsifier, which comprises the following specific steps: accurately weighing a certain amount of ferric chloride hexahydrate, mixed polyether demulsifier and multi-walled carbon nanotube, adding into a beaker together with a certain amount of solvent and assistant, carrying out ultrasonic treatment for a period of time to uniformly mix, adding into a reaction kettle with a polytetrafluoroethylene lining, and carrying out ultrasonic treatment for a period of time to obtain the magnetic response polyether demulsifier. Then introducing nitrogen for purging replacement, putting the reaction kettle into a drying oven, heating to a certain temperature, reacting for a certain time, cooling to room temperature after the reaction is completed, taking out, washing with an ethanol-water solution for multiple times, and drying to finally prepare the novel magnetic response polyether demulsifier. The prepared novel magnetic response polyether demulsifier has a good demulsification effect on thick oil emulsion with the water content higher than 90%, and under the action of an external magnetic field, rapid demulsification can be achieved, and recycling is easy to achieve.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of demulsifier preparation, and in particular to a preparation method and application of a novel magnetic responsive polyether demulsifier. Background Art

[0002] Petroleum is a non-renewable energy source and basic chemical raw material. With the continuous development of tertiary oil recovery technology and the continuous development of oil fields, the water content in crude oil production fluid has gradually increased, and the main type of emulsion has changed from water-in-oil type (W / O type) to oil-in-water type (O / W type). When dealing with such emulsions with high water content and complex components, the effective carrying load of equipment such as pumps, pipelines, and storage tanks is greatly reduced, and the service life of various pipelines and production equipment will also be reduced. Therefore, demulsification and dehydration must be carried out before oil transportation and refining. The demulsification methods of crude oil emulsions mainly include mechanical methods, physical methods, and chemical methods, among which chemical demulsification is currently the most commonly used demulsification and dehydration method. In the later stage of oil field exploitation, the properties of the produced crude oil change greatly, and the content of emulsified substances such as colloids, asphaltene, cyclohexane acid, soaps, etc. in the oil increases, and the properties of oil-water emulsions become more and more complex. Therefore, the requirements for demulsifiers used in the process of crude oil demulsification and dehydration are also getting higher and higher. The demulsification effects of a large number of existing demulsifiers are difficult to meet the production needs of oil fields. At present, it is difficult for demulsifiers with relatively mature production processes and relatively simple structures to have strong surface activity, sufficient flocculation ability and good agglomeration ability at the same time. It is difficult to effectively demulsify crude oil emulsions with increasingly complex components. In addition, high molecular weight chemical demulsifiers remain in the water phase or oil phase after use. The demulsifiers remaining in the oil phase greatly affect the oil quality. The demulsifiers remaining in the water phase are re-injected with water, which has an adverse effect on the recovery of crude oil. Summary of the invention

[0003] The purpose of the present invention is to provide a preparation method of a novel magnetic responsive polyether demulsifier and its products and applications in view of the above shortcomings.

[0004] The invention provides a method for preparing a novel magnetic responsive polyether demulsifier, which comprises the following specific steps: (1) preparing a mixed polyether demulsifier: fixing a three-necked flask with a condensation reflux device in a water bath, weighing polymethyl hydrogen siloxane, allyloxy polyoxyethylene ether, allyl polyethylene glycol diglycidyl ether, propylene glycol polyoxyethylene polyoxypropylene block polyether, cationic polyamine demulsifier and isopropanol, adding the mixture into the three-necked flask, heating and stirring to make the mixture uniform, adding acrylic acid, then adding catalyst p-toluenesulfonic acid and chloroplatinic acid solution, adding hydroquinone as an inhibitor for acrylic acid modification, stirring and heating to react, and after the reaction is completed, obtaining a crude mixed polyether demulsifier, and refining to obtain a finished mixed polyether demulsifier;

[0005] (2) Preparation of a novel magnetically responsive polyether demulsifier: Weigh ferric chloride hexahydrate, a finished mixed polyether demulsifier, multi-walled carbon nanotubes, a solvent and an additive and add them to a beaker. Ultrasonicate for a period of time to mix them evenly. Then add them to a polytetrafluoroethylene-lined reactor. Then, introduce nitrogen to purge and replace the mixture. Place the reactor in an oven for heating and reaction. After the reaction is completed, cool it to room temperature, take it out, rinse it with an ethanol-water solution several times, and finally obtain a novel magnetically responsive polyether demulsifier after drying.

[0006] Furthermore, in the step (1), the preparation method of the cationic polyamine demulsifier is as follows: the preparation steps of the cationic polyamine demulsifier in step S1 are as follows: a certain amount of dimethylamine, dodecylamine, and polyethylene polyamine are added to a three-necked flask and stirred for 15 to 20 minutes, epichlorohydrin is added dropwise at a temperature of 30 to 50°C and stirred for 1 hour, the temperature is raised to 80 to 85°C and kept for a period of time, and then the reaction is stopped to obtain the cationic polyamine demulsifier. The mass fraction ratio of dimethylamine: dodecylamine: epichlorohydrin: polyethylene polyamine in the cationic polyamine demulsifier is 45:7:43:5. The stirring time is 15 to 20 minutes, the reaction temperature is 80 to 85°C, and the reaction time is 4 to 5 hours.

[0007] 3. Further, in the step (1), the amount of each raw material added is: weigh 2.41g polymethyl hydrogen siloxane, 2.91g allyloxy polyoxyethylene ether, 2.45g allyl polyethylene glycol diglycidyl ether, 8.56g propylene glycol polyoxyethylene polyoxypropylene block polyether, 1.12 cationic polyamine demulsifier and 30ml isopropanol, add to a three-necked flask, heat and stir to mix evenly, add 0.63g acrylic acid, the amount of catalyst is 0.06g p-toluenesulfonic acid, the concentration of chloroplatinic acid solution is 4g / L, and the amount is 0.2ml. The amount of catalyst is 0.06g p-toluenesulfonic acid, the concentration of chloroplatinic acid solution is 4g / L, and the amount is 0.2ml.

[0008] Furthermore, in step (1), the specific conditions for heating and stirring to achieve uniform mixing are: heating to 40-60° C. and stirring for 20-40 minutes.

[0009] Furthermore, in the step (1), the amount of hydroquinone used is 0.02 to 0.04 g.

[0010] Furthermore, in the step (1), the stirring and heating reaction conditions are: heating to 75-85° C. and reacting for 6-10 hours.

[0011] Furthermore, in the step (1), the refining method is: dissolving the obtained crude mixed polyether demulsifier in dichloromethane, adding the mixture into a separatory funnel, adjusting the pH to neutral with a sodium hydroxide solution, standing the mixture to separate the layers, separating the lower layer of liquid, and obtaining the mixed polyether demulsifier after distillation.

[0012] Furthermore, in the step (2), the mass ratio of ferric chloride hexahydrate, the mixed polyether demulsifier product and the multi-walled carbon nanotubes is 1:0.5 to 1:0.1 to 0.2, and the mass ratio of anhydrous sodium acetate to ferric chloride hexahydrate is 2 to 3:1.

[0013] Furthermore, in the step (2), the reaction temperature is 200-240° C., and the reaction time is 8-10 h.

[0014] The second aspect of the present invention provides a use of a demulsifier prepared by the novel magnetic responsive polyether demulsifier preparation method, specifically for demulsifying high water-containing crude oil emulsions.

[0015] Beneficial effects of the present invention:

[0016] A preparation method of a novel magnetic responsive polyether demulsifier provided by the present invention

[0017] (1) The reaction conditions are mild and involve multiple chemical reactions. Among them, hexahydrated ferric chloride (FeCl3·6H2O) and anhydrous sodium acetate (CH3COONa) can be reacted at high temperature in ethylene glycol solvent to synthesize Fe3O4 magnetic nanoparticles. In this process, hexahydrated ferric chloride provides an iron source, anhydrous sodium acetate participates in the reaction as an alkali source, and ethylene glycol acts as a solvent and a reducing agent, which helps to form stable nanoparticles. Secondly, the mixed polyether demulsifier is grafted with Fe3O4. Certain functional groups (such as hydroxyl and amino) on the molecules of the mixed polyether demulsifier react with certain groups (such as hydroxyl) on the surface of the Fe3O4 magnetic nanoparticles to form chemical bonds and are grafted on the surface of Fe3O4 to form a polyether demulsifier with magnetic responsiveness.

[0018] (2) Multi-walled carbon nanotubes (MWCNTs) have a porous structure and a large specific surface area. They have the ability to combine with a variety of functional materials. During the reaction process, they can combine with polyether and Fe3O4 by physical adsorption or chemical bonding to form a composite material. Among them, the use of ferric chloride hexahydrate to generate Fe3O4 as a magnetic material has better controllability than directly using ready-made Fe3O4 as a magnetic material. The generated Fe3O4 can be more evenly dispersed in the new magnetic responsive polyether demulsifier, and its raw materials are easy to obtain and the preparation process is flexible.

[0019] (3) The branched polyether demulsifier coated on the magnetic material (Fe3O4) is used in combination with multi-walled carbon nanotubes. First, the multi-walled carbon nanotubes with a porous structure and a large specific surface area can better contact with the water phase in the emulsion. The branched polyether demulsifier and magnetic particles Fe3O4 loaded thereon, under the multiple effects of the demulsifier and the magnetic material, make the water-in-oil type heavy oil emulsion unstable and decompose into hydrophilic or lipophilic groups, and the tiny oil particles aggregate to form large oil droplets, thereby achieving rapid demulsification. It has a good demulsification effect on high-water content O / W emulsions. In addition, because of its magnetic response effect, it can be recycled by an external magnetic field, reducing the problem of demulsifier remaining in the water phase or oil phase, and has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 The flowchart of the preparation method of the novel magnetic responsive polyether demulsifier of the present invention;

[0021] Figure 2 The XRD spectrum of the novel magnetic responsive polyether demulsifier prepared in Example 2 of the present invention;

[0022] Figure 3 The FI-IR spectrum of the novel magnetic responsive polyether demulsifier prepared in Example 2 of the present invention; DETAILED DESCRIPTION

[0023] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the examples in the specification. The methods described are all conventional methods unless otherwise specified, and the original photocatalysts can be obtained from public commercial channels unless otherwise specified.

[0024] The term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0025] The preparation method of the novel magnetic responsive polyether demulsifier provided by the present invention comprises the following specific steps:

[0026] (1) Preparation of mixed polyether demulsifier: A three-necked flask with a condensation reflux device was fixed in a water bath, 2.41 g of polymethyl hydrogen siloxane, 2.91 g of allyloxy polyoxyethylene ether, 2.45 g of allyl polyethylene glycol diglycidyl ether, 8.56 g of propylene glycol polyoxyethylene polyoxypropylene block polyether, 1.12 g of cationic polyamine demulsifier and 30 ml of isopropanol were weighed and added to the three-necked flask, heated and stirred to mix evenly, 0.63 g of acrylic acid was added, followed by adding catalyst p-toluenesulfonic acid and chloroplatinic acid solution, and hydroquinone was added as an inhibitor of acrylic acid modification, stirred and heated to react, and after the reaction was completed, a crude mixed polyether demulsifier was obtained, which was refined to obtain a finished mixed polyether demulsifier.

[0027] In this step, the catalyst p-toluenesulfonic acid promotes the esterification reaction to introduce unsaturated double bonds, and then the catalyst chloroplatinic acid promotes the hydrosilylation reaction to combine the branched polyether with the main chain polymethylhydrogensiloxane. The added hydroquinone as an inhibitor can prevent free radical polymerization, slow down the reaction rate, and ensure the purity of the product.

[0028] (2) Preparation of a novel magnetically responsive polyether demulsifier: Weigh ferric chloride hexahydrate, a finished mixed polyether demulsifier, multi-walled carbon nanotubes, a solvent and an additive and add them to a beaker. Ultrasonicate for a period of time to mix them evenly. Then add them to a polytetrafluoroethylene-lined reactor. Then, introduce nitrogen to purge and replace the mixture. Place the reactor in an oven for heating and reaction. After the reaction is completed, cool it to room temperature, take it out, rinse it with an ethanol-water solution several times, and finally obtain a novel magnetically responsive polyether demulsifier after drying.

[0029] In this step, ferric chloride hexahydrate (FeCl·6H2O) and anhydrous sodium acetate (CH3COONa) react at high temperature in ethylene glycol solvent to synthesize Fe3O4 magnetic nanoparticles. In this process, ferric chloride hexahydrate provides an iron source, anhydrous sodium acetate participates in the reaction as an alkali source, and ethylene glycol acts as a solvent and a reducing agent, which helps to form stable nanoparticles. Secondly, the mixed polyether demulsifier is grafted with Fe3O4. Certain functional groups (such as hydroxyl groups and amino groups) on the molecules of the mixed polyether demulsifier react with certain groups (such as hydroxyl groups) on the surface of the Fe3O4 magnetic nanoparticles to form chemical bonds and are grafted on the surface of Fe3O4 to form a polyether demulsifier with magnetic responsiveness. Multi-walled carbon nanotubes (MWCNTs) can combine with polyether and Fe3O4 by physical adsorption or chemical bonding during the reaction to form a composite material. Among them, the use of ferric chloride hexahydrate to generate Fe3O4 as a magnetic material has better controllability than directly using ready-made Fe3O4 as a magnetic material. The generated Fe3O4 can be more evenly dispersed in the new magnetic responsive polyether demulsifier, and its raw materials are easy to obtain and the preparation process is flexible.

[0030] The following is a detailed description of the raw material feeding amount and the specific reaction conditions in the examples.

[0031] Example 1

[0032] Preparation of a new type of mixed demulsifier

[0033] (1) Preparation of cationic polyamine demulsifier: Add a certain amount of dimethylamine 45g, dodecylamine 7g, polyethylene polyamine 43g into a three-necked flask and stir for 15-20min. Add 5g of epichlorohydrin dropwise at 30-50°C and continue stirring for 1h. Then, raise the temperature to 80-85°C and react for 4-5h to obtain a cationic polyamine demulsifier.

[0034] Cationic polyamine demulsifier can be used as a promoter of epoxy ring-opening reaction, and undergoes epoxy ring-opening reaction with the epoxy group in allyl polyethylene glycol diglycidyl ether in the polyether demulsifier, and is grafted onto the polyether molecule to form a polymer.

[0035] (2) A three-necked flask with a condensation reflux device was fixed in a water bath, and 2.41 g of polymethylhydrogensiloxane, 2.91 g of allyloxy polyoxyethylene ether, 2.45 g of allyl polyethylene glycol diglycidyl ether, 8.56 g of propylene glycol polyoxyethylene polyoxypropylene block polyether, 1.12 g of the prepared cationic polyamine demulsifier and 30 ml of isopropanol were accurately weighed and added to the three-necked flask, heated and stirred at 50°C for 20 min, 0.63 g of acrylic acid was added, followed by 0.06 g of p-toluenesulfonic acid as a catalyst and 0.2 ml of 4 g / L chloroplatinic acid solution, and 0.03 g of hydroquinone was added to the three-necked flask as an inhibitor of acrylic acid modification, and the temperature was raised to 80°C with stirring and reacted for 8 h. After the reaction was completed, a crude mixed polyether demulsifier was obtained. The obtained crude mixed polyether demulsifier was dissolved in dichloromethane and added into a pear-shaped separatory funnel. The pH was adjusted to neutral with 0.5 mol / L sodium hydroxide solution. The mixture was allowed to stand for stratification, and the lower layer of liquid was separated. The finished mixed polyether demulsifier was obtained after distillation.

[0036] Example 2

[0037] Preparation of a new magnetically responsive polyether demulsifier

[0038] Take a beaker, accurately weigh 2.70g of ferric chloride hexahydrate, 1.03g of mixed polyether agent, 0.10g of carbon nanotubes, 6.03g of anhydrous sodium acetate and 30mL of ethylene glycol, add them to the beaker, ultrasonicate them in an ultrasonic cleaner for 20min to make them fully mixed, add them to a polytetrafluoroethylene-lined reactor, then introduce nitrogen to purge and replace for 20min, put the sealed reactor into an oven and heat it to 200℃, react for 6h, cool it to room temperature after the reaction is completed, take it out, rinse it with ethanol-water solution several times, and finally obtain a new magnetic responsive polyether demulsifier after drying. Sampling and testing.

[0039] Figure 2 The XRD spectrum of the magnetic responsive polyether demulsifier in this embodiment. Among them, the diffraction peaks appear at 18.31°, 30.12°, 35.48°, 43.12°, 57.03°, and 62.63°, which are consistent with the Fe3O4 standard spectrum of JCPDS (75-0033), and the corresponding crystal planes are (111), (220), (311), (400), (511), and (440). Among them, the diffraction peak of the magnetic responsive polyether demulsifier compared with the diffraction peak of Fe3O4 is narrowed, which may be because the addition of branched polyether changes the size of the crystalline particles.

[0040] Figure 3 The Fourier transform infrared spectrum of the magnetic responsive polyether demulsifier in this embodiment. Among them, the stretching vibration absorption peak of -OH is at 3435.36cm-1; the characteristic peak at 2970.47cm-1 may correspond to the stretching vibration absorption peak of CH in -CH3 or -CH2; the characteristic peak at 1630.52cm-1 may be the stretching vibration peak of C=O; there is a -COC absorption peak at 1272.60cm-1; the strong absorption peaks at 1123.32cm-1 and 1039.43cm-1 correspond to the stretching vibration peak of CO in the polyether, which shows that PO and EO are successfully grafted on the surface of the magnetic material particles; the absorption peak at 619.42cm-1 corresponds to the stretching vibration peak of the Fe-O bond.

[0041] Depend on Figure 2 XRD and Figure 3 The FT-IR spectrum of the magnetically responsive polyether demulsifier can illustrate the successful preparation of the magnetically responsive polyether demulsifier and the successful attachment of the branched polyether to the surface of the Fe3O4 particles.

[0042] Example 3

[0043] Take a beaker, accurately weigh 2.70g of ferric chloride hexahydrate, 1.03g of mixed polyether agent, 0.20g of carbon nanotubes, 6.01g of anhydrous sodium acetate and 30mL of ethylene glycol, add them to the beaker, ultrasonicate them in an ultrasonic cleaner for 20 minutes to fully mix them, add them to a polytetrafluoroethylene-lined reactor, then introduce nitrogen to purge and replace for 20 minutes, put the sealed reactor into an oven and heat it to 200°C, react for 8 hours, cool to room temperature after the reaction is completed, take out, rinse with ethanol-water solution several times, and finally obtain a new magnetic responsive polyether demulsifier after drying.

[0044] Example 4

[0045] Take a beaker, accurately weigh 2.70g of ferric chloride hexahydrate, 1.01g of mixed polyether agent, 0.20g of carbon nanotubes, 6.01g of anhydrous sodium acetate and 30mL of ethylene glycol, add them to the beaker, ultrasonicate them in an ultrasonic cleaner for 20 minutes to fully mix them, add them to a polytetrafluoroethylene-lined reactor, then introduce nitrogen to purge and replace for 20 minutes, put the sealed reactor into an oven and heat it to 200°C, react for 10 hours, cool to room temperature after the reaction is completed, take out, rinse with ethanol-water solution several times, and finally obtain a new magnetic responsive polyether demulsifier after drying.

[0046] Example 5

[0047] Take a beaker, accurately weigh 2.70g of ferric chloride hexahydrate, 1.01g of mixed polyether agent, 0.20g of carbon nanotubes, 6.01g of anhydrous sodium acetate and 30mL of ethylene glycol, add them to the beaker, ultrasonicate them in an ultrasonic cleaner for 20 minutes to fully mix them, add them to a polytetrafluoroethylene-lined reactor, then introduce nitrogen to purge and replace for 20 minutes, put the sealed reactor into an oven and heat it to 220°C, react for 6 hours, cool to room temperature after the reaction is completed, take out, rinse with ethanol-water solution several times, and finally obtain a new magnetic responsive polyether demulsifier after drying.

[0048] Example 6

[0049] Take a beaker, accurately weigh 2.70g of ferric chloride hexahydrate, 1.01g of mixed polyether agent, 0.20g of carbon nanotubes, 6.01g of anhydrous sodium acetate and 30mL of ethylene glycol, add them to the beaker, ultrasonicate them in an ultrasonic cleaner for 20 minutes to fully mix them, add them to a polytetrafluoroethylene-lined reactor, then introduce nitrogen to purge and replace for 20 minutes, put the sealed reactor into an oven and heat it to 220°C, react for 8 hours, cool to room temperature after the reaction is completed, take out, rinse with ethanol-water solution several times, and finally obtain a new magnetic responsive polyether demulsifier after drying.

[0050] Example 7

[0051] Take a beaker, accurately weigh 2.70g of ferric chloride hexahydrate, 1.01g of mixed polyether agent, 0.2g of carbon nanotubes, 6.01g of anhydrous sodium acetate and 30mL of ethylene glycol, add them to the beaker, ultrasonicate them in an ultrasonic cleaner for 20 minutes to fully mix them, add them to a polytetrafluoroethylene-lined reactor, then introduce nitrogen to purge and replace for 20 minutes, put the sealed reactor into an oven and heat it to 220°C, react for 10 hours, cool to room temperature after the reaction is completed, take out, rinse with ethanol-water solution several times, and finally obtain a new magnetic responsive polyether demulsifier after drying.

[0052] Experimental Example 1

[0053] (1) Preparation of simulated heavy oil emulsion: Weigh 0.1g of sodium dodecylbenzene sulfonate and 0.2g of polyacrylamide, fully dissolve them in 90g of water, add 10g of crude oil, and emulsify for 15min at 8000rpm using a high shear dispersing emulsifier to prepare an oil drop mother liquor with an oil content of 10%. Then weigh 10g of the oil drop mother liquor and 490g of water, put them into a 1000mL beaker, move them to a constant temperature water bath and preheat for 30min. The preheating temperature is consistent with the emulsification setting temperature, and the control temperature is 80°C. The preheated mixed liquid was stirred at a stirring intensity of 10000r / min and a stirring time of 20min. The prepared heavy oil emulsion was allowed to stand at room temperature for a period of time for subsequent demulsification research. The prepared simulated heavy oil emulsion had good stability within 72h, and its water content was ≥90% after being determined by Karl Fischer Coulometry. The oil content of the simulated heavy oil emulsion was <2000mg / L determined by an infrared oil measuring instrument.

[0054] (2) Take 6 25 mL stoppered colorimetric tubes, add 25 mL of the simulated heavy oil emulsion prepared in step (1) to each tube, weigh 5 mg of the new magnetic responsive polyether demulsifier prepared in Examples 2 to 7, and prepare a sample with a usage of 2000 mg / L of the new magnetic responsive polyether demulsifier. When the demulsification temperature is 60°C and the demulsification time is 60 min, compare the demulsification effects.

[0055] Serial number Oil content after demulsification (mg / L) Demulsification rate % Example 2 189.28 90.54 Example 3 103.45 94.83 Example 4 89.56 95.52 Example 5 63.89 96.81 Example 6 35.32 98.23 Example 7 40.65 97.97

[0056] Table 1 shows the demulsification effect of the magnetic responsive polyether demulsifier prepared under different conditions on the simulated high water-containing heavy oil emulsion with an oil content of 2000 mg / L

[0057] From the demulsification effects of different magnetically responsive polyether demulsifiers in Examples 2 to 7 above, it can be seen that when the added mass ratio of the mixed polyether agent and the multi-walled carbon nanotubes in the magnetically responsive polyether demulsifier is 1:0.2, its demulsification performance for high water content emulsions is better than that of the mass ratio of 1:0.1.

[0058] The demulsification rate WE% was calculated to investigate the demulsification effect of the magnetic responsive polyether demulsifier on the high water-content heavy oil emulsion. The magnetic responsive polyether demulsifier first adsorbs and wets the interface between the oil droplets and the water droplets in the emulsion through its polyether part, reducing the interfacial tension and destroying the stability of the interfacial film. Under the action of the polyether demulsifier, the oil droplets aggregate and form larger oil droplets. At the same time, the magnetic nanoparticles use their magnetic responsiveness to drag the oil droplets to move in a directional manner under the action of the external magnetic field, thereby achieving rapid aggregation of the oil droplets. As the oil droplets aggregate and migrate, they are eventually separated from the aqueous phase. Due to the presence of magnetic Fe3O4, the magnetic responsive polyether demulsifier can be recycled and reused through an external magnetic field, thereby improving resource utilization.

[0059] The calculation formula of demulsification rate WE% is:

[0060] Wherein WE% is the demulsification rate of the demulsifier; C0 is the oil content of the initial heavy oil emulsion (the initial heavy oil emulsion is the emulsion before the demulsifier is added before the experiment), in mg / L; C1 is the oil content of the heavy oil emulsion after the demulsifier is added, in mg / L.

[0061] (3) Preparation of new mixed demulsifier dilution: Weigh 10 g of the new mixed demulsifier, dissolve it in distilled water, transfer it into a 100 mL volumetric flask, and use distilled water to make up the volume to prepare a new mixed demulsifier solution with a mass fraction of 10% for demulsification experiments.

[0062] (4) The prepared simulated heavy oil emulsion was transferred into multiple 25 mL stoppered colorimetric tubes, and different volumes of the new mixed demulsifier and different masses of the magnetic responsive polyether demulsifier were added to the colorimetric tubes respectively. The demulsification temperature (20-80°C) was adjusted using a digital constant temperature water bath, and the oil-water stratification was observed within a certain period of time (10-60 min). The demulsification performance of the mixed demulsifier was measured under different conditions.

[0063]

[0064] Table 2 shows the demulsification efficiency of the new mixed polyether demulsifier and the magnetic response polyether demulsifier at different addition amounts at a demulsification temperature of 60°C and a time of 30 min.

[0065] As can be seen from the above table, since the magnetic response polyether demulsifier is a solid demulsifier, its demulsification efficiency is lower than that of the liquid mixed polyether demulsifier at a lower addition amount, but the new mixed demulsifier dilution is close to the maximum demulsification effect when the addition amount is 1000mg / L, and the demulsification rate is maintained at about 90%. The demulsification rate does not change significantly when the demulsifier addition amount continues to increase. This is because excessive demulsifier molecules will form a new interfacial film, hindering the aggregation and separation of oil droplets, resulting in no significant change in the demulsification effect. The demulsification effect of the magnetic response polyether demulsifier is significantly better than that of the mixed polyether demulsifier as the addition amount increases. When the addition amount reaches 2000mg / L (i.e., 2g / L), the demulsifier efficiency for the simulated high-water-content heavy oil emulsion exceeds 98%. Continuing to increase the addition amount of the demulsifier, its demulsification rate is slightly reduced. This may be that when the demulsifier addition amount is too much, the demulsifier agglomerates at the oil-water interface, resulting in the additional demulsifier being unable to be effectively adsorbed, thereby reducing the demulsification efficiency. Compared with the mixed demulsifier diluent, the demulsification efficiency is enhanced and the demulsifier can be recycled through an external magnetic field, thereby reducing the problem of polyether demulsifier remaining in the water phase or the oil phase.

[0066]

[0067] Table 3 shows the demulsification efficiency of the new mixed demulsifier dilution at the optimal addition amount of 1000 mg / L and the magnetic response polyether demulsifier at the optimal addition amount of 2 g / L and the demulsification time of 30 min at different temperatures

[0068]

[0069] Table 4 shows the demulsification efficiency of the new mixed demulsifier dilution at the optimal addition amount of 1000 mg / L and the magnetic response polyether demulsifier at the optimal addition amount of 2 g / L and the demulsification temperature of 60 ° C at different times

[0070] It can be seen from Tables 3 and 4 that the new mixed demulsifier has the best demulsification efficiency for high water-content heavy oil emulsion when the addition amount is 1000 mg / L, the demulsification temperature is 60°C, and the demulsification time is about 30 min. The optimal dosage of the magnetic response polyether demulsifier is 0.2 g / L. The demulsification efficiency at the same time and temperature is better than that of the mixed polyether demulsifier, and its maximum demulsification rate can exceed 98%.

[0071] A certain amount of magnetically responsive polyether demulsifier was added to a simulated heavy oil emulsion with an initial oil content of 2000 mg / L and transferred into multiple 25 mL stoppered colorimetric tubes to study the effect of different dosages (0.4-2.4 g / L) on the demulsification effect. After repeated recycling, the demulsification effect was still good.

[0072] Sample (g / L) Oil content after demulsification (mg / L) Demulsification rate % As is 2000 - 0.4 486.98 75.65 0.8 245.79 87.71 1.2 143.1 92.84 1.6 80.65 95.96 2 30.74 98.46 2.4 35.57 98.22

[0073] Table 5 shows the demulsification performance of high water-containing heavy oil emulsions with different addition amounts of magnetic responsive polyether demulsifier (60℃, 30min)

[0074] Use times Demulsification rate % 1 98.54 2 96.64 3 94.65 4 91.98 5 90.12

[0075] Table 6 shows the demulsification performance of the magnetic response polyether demulsifier on the high water-containing heavy oil emulsion in the repeated use test (60℃, 30min)

[0076] In summary, the demulsification parameters of the new magnetic responsive polyether demulsifier for high water-content heavy oil emulsions are: when the dosage of the magnetic responsive polyether demulsifier reaches 2g / L, the demulsification efficiency of the high water-content heavy oil emulsion is good, which can exceed 98%. Continuing to increase the amount of demulsifier added, the demulsification rate is slightly reduced. This may be that when the demulsifier is added in too much amount, the demulsifier agglomerates at the oil-water interface, resulting in the inability of the additional demulsifier to be effectively adsorbed, thereby reducing the demulsification efficiency. The new magnetic responsive polyether demulsifier was subjected to multiple rounds of "demulsification-recycling-re-demulsification" repeated use tests. After 5 cycles of use, the demulsification efficiency of the magnetic responsive polyether demulsifier for high water-content heavy oil emulsions remained at around 90%.

[0077] The novel magnetic response polyether demulsifier for demulsifying high-water-content heavy oil emulsion prepared by the present invention has a simple preparation process, has a good demulsification effect on high-water-content O / W emulsion, and because of its magnetic response effect, can be recycled through an external magnetic field, reducing the problem of demulsifier remaining in the water phase or the oil phase, and has good application prospects.

Claims

1. A method for preparing a novel magnetically responsive polyether demulsifier, characterized in that: The specific steps are: (1) Preparation of a mixed polyether demulsifier: a three-necked flask with a condensation reflux device is fixed in a water bath, polymethyl hydrogen siloxane, allyloxy polyoxyethylene ether, allyl polyethylene glycol diglycidyl ether, propylene glycol polyoxyethylene polyoxypropylene block polyether, cationic polyamine demulsifier and isopropanol are weighed and added to the three-necked flask, heated and stirred to mix evenly, acrylic acid is added, followed by adding catalysts p-toluenesulfonic acid and chloroplatinic acid solution, and hydroquinone is added as an inhibitor for acrylic acid modification, stirred and heated to react, and after the reaction is completed, a crude mixed polyether demulsifier is obtained, which is then refined to obtain a finished mixed polyether demulsifier; (2) Preparation of a novel magnetically responsive polyether demulsifier: Weigh ferric chloride hexahydrate, a finished mixed polyether demulsifier, multi-walled carbon nanotubes, a solvent and an additive and add them to a beaker. Ultrasonicate for a period of time to mix them evenly. Then add them to a polytetrafluoroethylene-lined reactor. Then, introduce nitrogen to purge and replace the mixture. Place the reactor in an oven for heating and reaction. After the reaction is completed, cool it to room temperature, take it out, rinse it with an ethanol-water solution several times, and finally obtain a novel magnetically responsive polyether demulsifier after drying.

2. A method for preparing the novel magnetic responsive polyether demulsifier according to claim 1, characterized in that: In the step (1), the preparation method of the cationic polyamine demulsifier is as follows: a certain amount of dimethylamine, dodecylamine and polyethylene polyamine are added into a three-necked flask and stirred for 15 to 20 minutes; epichlorohydrin is added dropwise at a temperature of 30 to 50° C. and stirred for reaction for 1 hour; the temperature is raised to 80 to 85° C. and the reaction is continued for 4 to 5 minutes, and then the reaction is stopped to obtain the cationic polyamine demulsifier, wherein the mass fraction ratio of dimethylamine: dodecylamine: epichlorohydrin: polyethylene polyamine in the cationic polyamine demulsifier is 45:7:43:

5.

3. The preparation method of the novel magnetic responsive polyether demulsifier according to claim 1, characterized in that: In the step (1), the amount of each raw material added is: weigh 2.41g of polymethyl hydrogen siloxane, 2.91g of allyloxy polyoxyethylene ether, 2.45g of allyl polyethylene glycol diglycidyl ether, 8.56g of propylene glycol polyoxyethylene polyoxypropylene block polyether, 1.12g of cationic polyamine demulsifier and 30ml of isopropanol, add them into a three-necked flask, heat and stir to mix evenly, then add 0.63g of acrylic acid, 0.06g of p-toluenesulfonic acid, 4g / L of chloroplatinic acid solution, and 0.2ml of the catalyst.

4. The preparation method of the novel magnetic responsive polyether demulsifier according to claim 1, characterized in that: In the step (1), the specific conditions for heating and stirring to achieve uniform mixing are: heating to 40-60° C. and stirring for 20-40 minutes.

5. The preparation method of the novel magnetic responsive polyether demulsifier according to claim 1, characterized in that: In the step (1), the amount of hydroquinone used is 0.02 to 0.04 g.

6. The method for preparing the novel magnetic responsive polyether demulsifier according to claim 2, characterized in that: In the step (1), the stirring and heating reaction conditions are: heating to 75-85° C. and reacting for 6-10 hours.

7. The method for preparing the novel magnetic responsive polyether demulsifier according to claim 2, characterized in that: In the step (1), the refining method is: dissolving the obtained crude mixed polyether demulsifier in dichloromethane, adding the mixture into a separatory funnel, adjusting the pH to neutral with a sodium hydroxide solution, standing the mixture to separate the layers, separating the lower layer of liquid, and obtaining the mixed polyether demulsifier after distillation.

8. The method for preparing the novel magnetic responsive polyether demulsifier according to claim 2, characterized in that: In the step (2), the mass ratio of ferric chloride hexahydrate, the mixed polyether demulsifier product and the multi-walled carbon nanotubes is 1:0.5 to 1:0.1 to 0.2, and the mass ratio of anhydrous sodium acetate to ferric chloride hexahydrate is 2 to 3:

1.

9. The method for preparing the novel magnetic responsive polyether demulsifier according to claim 2, characterized in that: In the step (2), the reaction temperature is 200-240° C. and the reaction time is 6-10 hours.

10. Use of a demulsifier prepared by the method for preparing a novel magnetic responsive polyether demulsifier according to any one of claims 1 to 9, characterized in that: Used for demulsification of high water content crude oil emulsion.

Citation Information

Cited By

  • Polystyrene-polyether core-shell structure demulsifier and preparation method thereof

    CN119931063A